TANGGUNGJAWAB PIDANA PELAKU TINDAK PIDANA PENCURIAN: PUTUSAN PERKARA NOMOR 590/Pid.B/2019/PN Sim - R.Rivaldi Aldanta; Frans Simangunsong (Gapenas Publisher, 2023)
A perpetrator is one who deliberately performs acts prohibited by the law, and can be performed alone or in groups with a supposed violation of the norm and is expressly referred to as a crime. Especially crimes common to social life are theft, resulting in large Numbers of victims. Stealing is one of the crimes of crime that can harm many because of losing their property or possessions. The responsibility for theft is based on the book of criminal law that the perpetrator must be responsible if the act meets the key elements that can be met according to article 362 of the criminal code and several others will be used asa consideration in using the chapters relating to theft by law enforcement. Interestingly, in the case of the theft, it was very rare for any criminal to have been convicted for his crimes on an estate that could enmeshed the theft by taking measures of plantation goods that were associated with the crime taken in the form of gum ram of a low grade item. But with the object of its object of very small value, the perpetrator can still be convicted. The study employed a normative-normative juridical method of legislation, conceptual, and case studies that doubtless dealt with responsibility to perpetrators of theft crimes. This study shows that law enforcement provides knowledge to all societies that the punishment for criminal crimes of theft still applies to anyone who commits a felony even with stolen goods or objects is of very little value, This can be taught that it still applies to idlers who are accused of theft, such as by legislation - the plantation law against the repurchaser of gum rambody who deliberately takes the plantation that belongs to a Japanese company standing in Indonesia and is therefore breaking the law